A organização internacional dos trabalhadores metalúrgicos na Mercedes-Benz: perspectivas de contra-hegemonia local-global - Rodrigues, Eduardo Magalhães [UNESP] (2013)
The present dissertation is focused on the experience of the international trade union organization of workers since Mercedes-Benz Brazil in São Bernardo do Campo. I highlight since because the very nature of the process led to the global connection with employees located at industrial units in foreigner countries of the same transnational company. Among several political players as well as in the academic world, there is the controversial issue about the importance of the union movement not only in Brazil, but also internationally. In other words, the main issue is about the effectiveness of international trade unionism in the presence of the capital hegemonic globalization. On one hand concerns if it is possible that this practice means an alternative to the hegemonic model, even being, nowadays, in an incipient stage. On the other hand if the international trade union perspective can contribute to the maintenance or new achievements of the workers. Such issues are strongly important, mainly in a world of intense and growing globalization of all sectors of society. There was an indication of positive responses to both questions above, suggesting that, despite the current worldwide crisis, involving the international trade union movement as well, is an feasible strategy and even essential to the worker. The methodology, besides the theoretical references, dealt with field research collecting primary data and interviews with the main protagonists of the international trajectory, which completes 30 years in 2014.